Unconscious inhibition separates two forms of cognitive control - Frederic Boy (Proceedings of the National Academy of Sciences, 2010)
In the human brain, cognitive-control processes are generally consid- ered distinct from the unconscious mechanisms elicited by subliminal priming. Here, we show that cognitive control engaged in situations of response con!ict interacts with the negative (inhibitory) phase of subliminal priming. Thus, cognitive control may surprisingly share common processes with nonconscious brain mechanisms. In contrast, our "ndings reveal that subliminal inhibition does not, however, interact with control adaptation—the supposed modulation of cur- rent control settings by previous experience of con!ict. Therefore, although in!uential models have grouped immediate cognitive con- trol and control adaptation together as products of the same con!ict detection and control network, their relationship to subliminal inhi- bition separates them. Overall, these results suggest that the impor- tant distinction lies not between cognitive or top-down processes on the one hand and nonconscious priming mechanisms on the other hand but between responsive (poststimulus) mechanisms that deal with sensorimotor activation after it has occurred and preparatory (prestimulus) mechanisms that are modulated before stimulus arrival.